Judicial law-making in European constitutional courts - Florczak-Wątor, Monika (Routledge, 2020)
"This book analyses the specificity of the law-making activity of European constitutional courts. The main hypothesis is that currently constitutional courts are positive legislators whose position in the system of State organs needs to be redefined"-- Provided by publisher.
Keywords: Constitutional courts -- Europe.; Judicial power -- Europe.; Political questions and judicial power -- Europe.; LAW / General; LAW / Administrative Law & Regulatory Practice; LAW / Civil Rights; Constitutional courts.; Judicial power.; Political questions and judicial power.; Europe.; Electronic books.